A freestanding hierarchically structured cathode enables high sulfur loading and energy density of flexible Li–S batteries. Issue 13 (20th March 2020) - Liu, Jianpeng; Li, Zhong; Jia, Beibei; Zhu, Juncheng; Zhu, Wenliang; Li, Jianping; Pan, Hao; Zheng, Bowen; Chen, Liangyin; Pezzotti, Giuseppe; Zhu, Jiliang
Abstract : Due to sulfur agglomeration and drastic volume expansion during charging, a significant challenge for lithium–sulfur battery applications is to achieve favorable energy densities while realizing substantial sulfur loading. Abstract : Due to sulfur agglomeration and drastic volume expansion during charging, a significant challenge for lithium–sulfur battery applications is to achieve favorable energy densities while realizing substantial sulfur loading. The rational design of cathode materials is therefore essential. Here we show a new type of low-cost sulfur/silica/carbon hybrid cathode by integrating carbon-coated and sulfur-encapsulated mesoporous SiO2 nanospheres with a carbon fiber cross-linked graphene framework (denoted as 3D-GCSS). The porous morphology of SiO2 ensures electrolyte accessibility, while the mechanical robustness of graphene and the carbon fiber contributes to structural sturdiness and flexibility. The synergistic effect exerted by polar SiO2 together with conductive graphene and the carbon fiber helps to confine sulfur and intermediate polysulfides as well as providing abundant charge transfer paths. Benefiting from these merits, a coin cell fabricated based on the freestanding 3D-GCSS with an 8 mg cm −2 sulfur content displayed a high capacity of 1462 mA h g −1 at 0.5C, satisfactory rate performance and cycling stability. More importantly, a type of ultra-flexible soft-packaged cell was assembled utilizing the 3D-GCSS electrode. At a considerable sulfur loading of 20 mg cm −2, the battery delivered an outstanding capacity of 2.15 A h, a gravimetric energy density of 371 W h kg −1 (1055 W h kg −1 based on the cathode) and a volumetric energy density of 582 W h l −1 .